1994
DOI: 10.1901/jeab.1994.62-269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Accessibility of Reinforcement Schedules on Choice in Humans

Abstract: Based on the delay-reduction hypothesis, a less profitable schedule should be rejected if its duration exceeds the mean delay to reinforcement. It should be accepted if its duration is shorter than the mean delay. This was tested for humans, using a successive-choice schedule. The accessibility of the less profitable (variable-interval 18 s) schedule was varied by changing the duration (in terms of a fixed interval) of the waiting-time component preceding its presentation. Forty-eight students were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 79 publications
4
19
0
Order By: Relevance
“…The present results therefore provide additional evidence that the predictions of optimal foraging models, including the energy-budget rule , generalize to choice in humans for monetary outcomes under a variety of conditions (e.g. , Jacobs & Hackenberg , 1996;Pietras & Hackenberg, 2001;Stockhorst, 1994;and see Winterhalder & Smith, 2000), including choice! in social contexts (e.g ., Kraft & Baum , 2001 ;Madden, Peden, & Yamaguchi, 2002 ;Sokolowski, Tonneau , & Freixa I Baque,1999).…”
Section: Discussionsupporting
confidence: 53%
“…The present results therefore provide additional evidence that the predictions of optimal foraging models, including the energy-budget rule , generalize to choice in humans for monetary outcomes under a variety of conditions (e.g. , Jacobs & Hackenberg , 1996;Pietras & Hackenberg, 2001;Stockhorst, 1994;and see Winterhalder & Smith, 2000), including choice! in social contexts (e.g ., Kraft & Baum , 2001 ;Madden, Peden, & Yamaguchi, 2002 ;Sokolowski, Tonneau , & Freixa I Baque,1999).…”
Section: Discussionsupporting
confidence: 53%
“…The response requirement to access the more profitable alternative (which turned off the tone on a VI 3s schedule) was held constant (FI 7.5s), while the requirement to access the less profitable alternative (which turned off the tone on a VI 18s schedule) was varied. Results were compatible with previous work exploring the same variables with pigeons: increased accessibility of the less profitable outcome led to decreased acceptability of that outcome (Stockhorst, 1994) In the laboratory and in the field, there is an indication that optimal diet theories are better at predicting foraging behavior in some species than others. After reviewing a wide range of studies covering a large number of species, Sih and Christensen (2001) concluded that such theories are best at predicting the foraging behavior of organisms that feed on immobile prey.…”
supporting
confidence: 85%
“…One issue of abiding interest involves the possible identification of a mechanism by which pigeons, rats (studied by Collier's group---see reference above) and humans (studied by Preston, 1989 andby Stockhorst, 1994) are sensitive to the more optimal outcome, for example, to the higher energy food item. Before discussing this issue, we clarify the distinction between the optimal-foraging and delayreduction approaches.…”
mentioning
confidence: 99%
“…Extensions of the DRH The DRH has been tested under several different procedures (Fantino et al, 1993) and has been extended to studies examining aversive consequences (Fantino, 1981;Stockhorst, 1994), observing Fantino, 1981, 1989;Fantino and Case, 1983), self-control (Navarick and Fantino, 1976;Ito and Asaki, 1982), percentage reinforcement (Spetch and Dunn, 1987;Dunn and Spetch, 1990;, three-alternative choice (Fantino and Dunn, 1983), simultaneous-encounter experiments (Fantino and Preston, 1989), and foraging, analyzed using successive-choice procedures (Abarca and Fantino, 1982;Fantino and Abarca, 1985). However, the DRH was first developed to account for choice between two simultaneously available variable interval schedules of reinforcement in the concurrent-chains procedure developed by Autor (1960) and Herrnstein (1964), hence its predictions should not be expected to hold for fixed schedules with comparable mean interreinforcement intervals (Fantino et al, 1993).…”
Section: The Delay-reduction Hypothesis (Drh)mentioning
confidence: 99%
“…Choice of the terminal link, at this juncture, is called 'acceptance'. A response on the first component stimulus button in the choice situation to return to the initial link constitutes a 'rejection', which initiates the beginning of the next trial starting again with the search phase (see also, Stockhorst, 1994).…”
Section: Concurrent-chains Versus Successive-choice Proceduresmentioning
confidence: 99%